PENGARUH SUHU ADSORPSI DAN JUMLAH PENAMBAHAN KARBON AKTIF TERHADAP KECERAHAN SURFAKTAN DECYL POLIGLIKOSIDA DARI D-GLUKOSA DAN DEKANOL (Jurnal Teknik Kimia USU, 2015)
Alkyl plyglycosides (APG) is a nonionic surfactant which is environmentally friendly. Carbohidrate source as APG’s raw material supplied the hydrophilic group, and fatty alcohol acted as hydrophobic group. Some undesirable compounds formed during the APG synthesis and caused dark color. In direct synthesis, D-glucose reacts directly with decanol in molar ratio of D-glucose:decanol is 1:5 and 0,5 % of HCl as catalist based on weight of D-glucose for 1 hour at reaction temperature about 95 oC. And then the solution is neutralized with NaOH 50 % on pH 8-10. Added activated carbon with variation 1, 3, 5, 7, and 9 % based on weight of solution at adsorption temperature with variation 30, 40, dan 50 oC, then filtrate and distilate the solution at vacuum condition. Product is analized using spectroscopy fourier transform infrared (FT-IR) and spectroscopy UV-Vis. The highest percent of transmittance is about 44,90 % obtained at adsorption temperature 50 oC and amount of activated carbon 3 %.